99 Perfecting the Proforma – A Full-Cycle Audit on The Quality of Documentation of The Hand Trauma Proforma At the Regional Plastic Surgery Department. (12th October 2021) - Noshirwani, A; Phillips, B; Hosain, M; Drewniak, K; Parekh, V; Bell, D
Abstract: Aim: We aimed to assess the quality of record-keeping of the departments hand trauma proforma, identify areas of improvement, and to implement and assess the quality of an updated proforma. Method: Data from 101 parameters was collected for 20 patients undergoing surgery for an upper limb injury in November 2019. An updated proforma was implemented and a further 20 patients were analysed in February 2020. All fields were compared between two audit cycles and comments were collected. Results: The overall completion rate increased. Documentation of the responsible consultant increased to 100%, along with an increase in documenting of hobbies and injury mechanism. X-ray findings (55% to 85%) and antibiotic plan (35% to 80%) increased. Implementation of a free text box resulted in written descriptions of injury to compliment sketches. In the operation note, documentation of anaesthetic type used increased, along with tourniquet use and time. There was clearer documentation of the injury, findings, and procedure, with greater use of diagrams to illustrate the repair. There was a drop in the recording of post-op plans (100% to 85%), post-op antibiotics (90% to 75%), and follow-up plan (95% to 60%). Clinicians commented to increase the size of the free-text box and hand diagram on the operative page to facilitate easier drawings. Conclusions: The Hand Trauma Proforma has made good progress from its original version but requires further adjustments to ensure complete data input. It sets a high standard for data collection and presents itself as a useful tool for units across the United Kingdom.